2003
DOI: 10.1002/jcp.10208
|View full text |Cite
|
Sign up to set email alerts
|

HES and HERP families: Multiple effectors of the notch signaling pathway

Abstract: Notch signaling dictates cell fate and critically influences cell proliferation, differentiation, and apoptosis in metazoans. Multiple factors at each step-ligands, receptors, signal transducers and effectors-play critical roles in executing the pleiotropic effects of Notch signaling. Ligand-binding results in proteolytic cleavage of Notch receptors to release the signal-transducing Notch intracellular domain (NICD). NICD migrates into the nucleus and associates with the nuclear proteins of the RBP-Jk family (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
921
1
17

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,120 publications
(976 citation statements)
references
References 173 publications
(297 reference statements)
30
921
1
17
Order By: Relevance
“…The hairy/enhancer of split (Hes) genes are highly conserved proteins that are regulated by Notch in multiple cell types, reviewed in [7,8]. Hairy/Enhancer of split family genes were first described as neurogenic genes in Drosophila (like Notch, Deltex and Mastermind), since embryos lacking the function of these genes showed an increased number of neuroblasts at the expense of epidermal precursors, reviewed in [2,9].…”
Section: Notch Target Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…The hairy/enhancer of split (Hes) genes are highly conserved proteins that are regulated by Notch in multiple cell types, reviewed in [7,8]. Hairy/Enhancer of split family genes were first described as neurogenic genes in Drosophila (like Notch, Deltex and Mastermind), since embryos lacking the function of these genes showed an increased number of neuroblasts at the expense of epidermal precursors, reviewed in [2,9].…”
Section: Notch Target Genesmentioning
confidence: 99%
“…Hairy/Enhancer of split family genes were first described as neurogenic genes in Drosophila (like Notch, Deltex and Mastermind), since embryos lacking the function of these genes showed an increased number of neuroblasts at the expense of epidermal precursors, reviewed in [2,9]. Several lines of evidence have suggested that these genes are indeed direct Notch target genes: a) The promoters of Hes1, Hes5 and Hes7 as well as Hey1, Hey2 and HeyL (subfamily of Hes, related with YRPW motif) can be activated by a constitutive active form of Notch1 [10 -12], reviewed in [7]; constitutive active Notch describes a mutant of Notch that is continuously proteolytically processed and migrating to the nucleus, b) endogenous Hey1 and Hey2 show an upregulation by NICD in several different cell lines [13], c) in co-culture experiments with Notch-ligand expressing cells, that achieve a more physiological level of Notch signaling, these genes are upregulated as well [13 -15]; these experiments were also performed in the presence of cyclohexamide, an inhibitor of protein synthesis, to exclude secondary effects, d) k-secretase inhibitor DAPT, which prevents cleavage of Notch, was added to Tcell leukemia cell lines which show constitutive-active Notch signaling; subsequent microarray analysis identified again members of this transcription factor family as direct Notch target genes [16]. Therefore, in mammals, the best-described Notch target genes are indeed the transcription factors Hes1, Hes5 and Hey1 [8,17].…”
Section: Notch Target Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the ANK domain weakly interacts with both CSL and a shorter sequence at the N‐terminal end of mastermind‐like 1 (MAML1) protein (the transcriptional co‐activator)21, 22. The formed transcription activation ternary complex NICD/CSL/MAML1 further upregulates the target genes (such as HES/HEY transcriptional repressors 23), which is known as the canonical Notch signaling pathway 3.…”
Section: Notch Signalingmentioning
confidence: 99%